Production records of lambs from East African Blackhead ewes and Dorset Horn rams - Trail, J.C.M.; Sacker, G.D. (1966)
Dorset Horn rams were used on East African Blackhead sheep in western Uganda in mutton production through improved lamb growth. The crossbred lambs were significantly heavier than the indigenous at birth. From birth to weaning at five months, the growth rates of both types were identical, being 0.19lb; liveweight increased per day for single lambs. From weaning to one year of age the crossbreds grew at more than twice the rate of the indigenous, the daily liveweight increases of single lambs being 0.21 lb. for crossbreds and 0.08 lb for ther indigenous. The average weights of all lambs at one year were 76.1 lb for crossbreds and 45.0 lb for the indigenous. Mortality rates to weaning were similar but crossbreds suffered heavy losses from weaning to one year due to an outbreak of haemolytic jaundice, the cause of which was not established.